Synthesis of heterocycles via palladium-catalysed direct arylation - Yagoubi, M (2011)
Chapter 1 is a brief review on some of the recents developments in palladium-catalysed C-H functionalisation chemistry. The synthesis and functionalisation of heterocycles using these methodologies was particularly emphasised. Chapter 2 presents our efforts to identify a new catalytic system to promote the intramolecular coupling of vinyl bromides with unfunctionalised aryl C-H bonds for the formation of benzofurans. Dihydrobenzofurans were obtained efficiently under mild conditions in the presence of Pd(OAc)₂, X-Phos and K₂CO₃ in DMA at 80 °C and a subsequent one-pot isomerisation under acidic conditions afforded the desired benzofurans. A new strategy has also provided access to more complex benzofurans by functionalisation of the exocyclic alkene isomer in both a chiral and achiral manner. In Chapter 3, mechanistic studies were performed on the benzofuran formation reaction. The analysis of substituent effects on the aromatic ring is in accordance with an electrophilic aromatic substitution mechanism (SEAr); however, the existence of both intra and intermolecular kinetic isotope effects suggest a SE3 type pathway rather than a pure SEAr. In Chapter 4, the intramolecular coupling of vinyl bromides with unfunctionalised aryl C-H bonds was further extended to the synthesis of six-membered heterocycles by direct arylation of alkenyl bromide derivatives in the presence of Pd(OAc)₂, dppf and K₂CO₃ in DMA at 120 °C. The synthetic utility of this methodology was exemplified by the synthesis of substituted isoquinolines in six steps. Moreover, we have applied our methodology to the direct arylation of sulfonamides, leading to an interesting synthesis of widely used sultams. Both these new routes are currently being investigated and should provide access to a variety of differently substituted cyclic sulfonamides and isoquinolines. Finally, Chapter 5 presents a new strategy for the synthesis of benzo[b]furan was briefly investigated. It consists in consecutive Tsuji-Trost and C-H functionalisation reactions. This methodology requires simpler and more versatile substrates, allowing access to various heteroaromatics in a single step. We successfully proved the viability of this reaction through the synthesis of a range of benzofurans in modest yields. To our knowledge, this is the first example of a single palladium catalyst performing these different reactions in tandem in a simple procedure.